2013
DOI: 10.1021/am4007403
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Induced Photoluminescence and Singlet Oxygen Generation from Aggregated Gold Nanoparticles

Abstract: Metal nanoparticles have potential applications as bioimaging and photosensitizing agents. Aggregation effects are generally believed to be adverse to their biomedical applications. Here we have studied the aggregation effects on two-photon induced photoluminescence and singlet oxygen generation of Au nanospheres and Au nanorods of two different aspect ratios. Aggregated Au nanospheres and short Au nanorods were found to display enhanced two-photon induced photoluminescence and singlet oxygen generation capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 63 publications
4
64
1
Order By: Relevance
“…The results indicate that with different light irradiation, cells treated with 5-ALA-GNPs all produce more singlet oxygen than those treated with 5-ALA alone, and the cells incubated with GNPs alone nearly produce no singlet oxygen compared with the control (nontreated cells). Vankayala et al and Jiang et al showed that GNP itself can effectively generate singlet oxygen induced by light, 44,45 but in these papers, GNPs were usually induced by a UV light with a large irradiation power (around 100 W) and the generation of singlet oxygen was mainly the result of two-photon excitation instead of the mW level irradiation power with 502 and 635 nm wavelengths in our study. Green LED irradiation gives a greater improvement efficiency, whereas the SOG is about 2.74 times higher for conjugates than those of the PpIX alone.…”
Section: Ppix and Singlet Oxygen Generationcontrasting
confidence: 55%
“…The results indicate that with different light irradiation, cells treated with 5-ALA-GNPs all produce more singlet oxygen than those treated with 5-ALA alone, and the cells incubated with GNPs alone nearly produce no singlet oxygen compared with the control (nontreated cells). Vankayala et al and Jiang et al showed that GNP itself can effectively generate singlet oxygen induced by light, 44,45 but in these papers, GNPs were usually induced by a UV light with a large irradiation power (around 100 W) and the generation of singlet oxygen was mainly the result of two-photon excitation instead of the mW level irradiation power with 502 and 635 nm wavelengths in our study. Green LED irradiation gives a greater improvement efficiency, whereas the SOG is about 2.74 times higher for conjugates than those of the PpIX alone.…”
Section: Ppix and Singlet Oxygen Generationcontrasting
confidence: 55%
“…Comparatively, aggregated Au nanoparticles display enhanced two-photon photoluminescence (TPPL) due to plasmon coupling which is potential for bioimaging application. 38 In this case, TPPL microscopy was employed to provide evidence that Peptide-AuNPs can selectively recognize integrin on HEL cells' cytomembrane.…”
Section: Resultsmentioning
confidence: 99%
“…The result is in accordance with the previous study that aggregated Au nanospheres behaves rather broad TPPL spectrum ranged from 570 nm to 700 nm. 38,39 The nonlinear optical property of coupled Peptide-AuNPs allows us to deduce inhomogeneous spatial distribution of the integrin. In striking contrast, vacant cells do not emit noticeable photoluminescence 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 9 ( Figure 5b) when TPPL image was collected at the same setting as above (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the enhancement could be resulted from increased extinction at the excitation wavelength when excited at 730 nm. [ 50 ] …”
Section: Enhanced Two-photon Fluorescence Imaging Of Mn 3 [Co(cn) 6 ]mentioning
confidence: 99%